The correlation signal processing of the atmospheric radio acoustic temperature sensing systems - Карташов, В.М.; Бабкин, С.И.; Куля, Д.Н. (Radiotekhnika, 2012)
Methods for signal correlation processing of the temperature radio acoustic sensing systems are proposed and the features of these methods are analyzed. It is shown that for registration of the vertical profiles of air temperature with the resolution sufficient for the practice by the correlation method it is necessary to complicate the processing device of the scattered signals. It is pointed out that for more simple processing equipment appropriate to apply the tracking principle for the Bragg detuning parameter. The feature of tracking principle is the use of the values of the estimated parameters defined in the previous cycles of observation.